Medicago truncatula quantitative resistance to a new strain of Verticillium alfalfae from Iran revealed by a genome-wide association study - Fartash, Amir Hossein; Ben, Cécile; Mazurier, Mélanie; Ebrahimi, Asa; Ghalandar, Mojtaba; Gentzbittel, Laurent; Rickauer, Martina (Frontiers in Plant Science, 2023)
Verticillium wilt is a major threat to many crops, among them alfalfa (Medicago sativa). The model plant Medicago truncatula, a close relative of alfalfa was used to study the genetic control of resistance towards a Verticillium alfalfae isolate from Iran. New isolates of V. alfalfae were obtained from alfalfa fields in Iran and characterized. The Iranian isolate AF1 was used in a genome-wide association study (GWAS) involving 242 accessions from the Mediterranean region. Root inoculations were performed with conidia at 25 °C and symptoms were scored regularly. Comparison to a previous study with French isolate V31.2 at 20 °C showed high correlation with a shift to higher susceptibility, and similar geographical distribution of resistant and susceptible accessions, with resistant accessions mainly in the western part. GWAS revealed 30 significant SNPs linked to resistance towards isolate AF1. None of them were common to the previous study with isolate V31.2 at 20 °C. To confirm these loci, the expression of nine underlying genes was studied. All genes were induced in roots following inoculation, in susceptible and resistant plants. However, in resistant plants induction was higher and lasted longer. Taken together, the use of a new pathogen strain and a shift in temperature revealed a completely different genetic control compared to a previous study that demonstrated the existence of two major QTLs. These results can be useful for Medicago breeding programs to obtain varieties better adapted to future conditions.